“Obtención y caracterización de furfural a partir de coronta de maíz en la Región San Martín - Lescano Bocanegra, Lesslie Crostina (1998)
This research work is a theoretical - practical, aimed at obtaining furfural from the cob of corn. To such effect, the cob was subject to wia grinding for then be impregnated with solution acid at different concentrations. T .to mixture was subjected to a first distillation by arra.' steam ltre collecting 695 m1. in a time of 2.20 hours and at a temperature of 105° C using as heating medium burnt lubricating oil. Neutrnliz.Amos the distillate with 24.2 g. sodium carbonate and saturated with 99.2 gr. of sodium chloride. It is distilled again this dissolution vacuum at a temperature of 76° C, and lma 68 pressure. 5 mrnHg, collecting about 542 mi. of liquid that it is saturated with 91.4 Gr. of sodium chloride and is exhausted with 215 mi. ethyl ether. The third distillation to recover used ether, being the recovery of 55.81% by volume, leaving as residue the furfural, which is dried with 1.32 Gr. chloride...